Metastatic extrapleural malignant solitary fibrous tumor presenting with hypoglycemia (Doege–Potter syndrome) - Andrew J. Degnan, MD, MPhil; Kenneth K.W. Lee, MD; Marta I. Minervini, MD; Amir A. Borhani, MD (Radiology Case Reports, 2017)
We report a rare case of metastatic malignant solitary fibrous tumor (SFT) that presented with hypoglycemia because of insulin growth factor-2 production. Initial workup included computed tomography imaging that revealed a large, partially necrotic liver mass, a hypervascular pancreatic head lesion, and 2 renal lesions. Following hepatic resection, pancreatic head resection and nephrectomy, all these lesions demonstrated pathological findings that were consistent with SFT. The patient also had a history of an intracranial mass that had been previously resected and treated with gamma knife therapy at an outside institution, which was found to also be SFT. Six months after initial pancreatic head resection, the patient developed a new lesion involving the pancreatic tail that was found to represent recurrent metastatic SFT. This case emphasizes the highly aggressive nature of extrapleural SFT, while rare, and the role of imaging in follow-up for disease recurrence.